A Study on the Occurrence of Poultry Diseases in Sylhet Region of Bangladesh - Islam, M.R.; Das, B.C.; Hossain, K.; Lucky, N.S.; Mostafa, M.G. (International Journal of Poultry Science, 2003)
A pathological investigation on the occurrence of poultry diseases in Sylhet region of Bangladesh was conducted during the period from November 2001 to October 2002. A total of 1352 sample of either dead or sick birds were brought from different Upazillas of Sylhet region. Diagnosis of different disease conditions was made on the basis of the history, age of birds, clinical signs, gross and microscopic lesions. The diagnosed diseases included Infectious Bursal disease (IBD) (24.26%), Newcastle Disease (ND) (6.73%), Infectious Bronchitis (0.29%), Omphalitis (2.81%), Fowl Cholera (0.44%), Salmonellosis (6.73%), Colibacillosis (5.17%), Necrotic enteritis (0.44%), Aspergillosis (17.53%), Infectious Coryza (0.37%), Chronic respiratory disease (CRD)/Mycoplasmosis (5.32%), Coccidiosis (9.46%) and deficiency disorders/stress condition (1.03%). In general, the highest number of cases were recorded in the age group of 8-21 days (42.60%), followed by 22-35 days age group (26.62%), 0-7 days age group (26.10%), 36-60 days age group (1.03%) and over 60 days age group (3.62%) of Poultry. Distribution and proportionate incidence of poultry disease of Bangladesh reveals that the poultry diseases occur mostly in rainy season (56.36%), followed by summer (28.11%) and the least in winter season (15.53%).